IgE sensitization to food allergens and airborne allergens in relation to biomarkers of type 2 inflammation in asthma. Issue 9 (6th June 2018) - Patelis, A.; Alving, K.; Middelveld, R.; James, A.; Ono, J.; Ohta, S.; Izuhara, K.; Borres, M. P.; Forsberg, B.; Janson, C.; Malinovschi, A.
Summary: Background: We have recently reported that sensitization to food allergens and sensitization to airborne allergens had independent associations with increased fraction of exhaled nitric oxide (FeNO) and blood eosinophils in middle‐aged adults and in young subjects with asthma. Objective: To investigate the relation between IgE sensitization and several type 2 inflammation biomarkers in adult asthmatics. Methods: FeNO, urinary eosinophil‐derived neurotoxin (U‐EDN), serum eosinophil cationic protein (S‐ECP) and periostin were measured in 396 asthmatics, aged 17‐76 years, from the Swedish GA2LEN study. Sensitization to airborne allergens was examined with skin prick tests (≥3 mm wheal) and sensitization to food allergens with measurement of specific IgE (≥0.35 kU/L). Results: Asthmatics sensitized to food allergens had higher FeNO, 22.3 ppb (18.6, 26.7) vs 16.1 ppb (14.2, 18.2) ( P = .005), S‐ECP, 17.7 mg/L (14.8, 21.1) vs 12.8 mg/L (10.9, 14.9) ( P = .01), and periostin, 73.7 (67.5, 80.3) ng/mL vs 59.9 (55.8, 64.2) ng/mL ( P = .003), than non‐sensitized subjects. Periostin levels in this group were also significantly higher than in the group sensitized only to airborne allergens ( P = .01). Sensitization to food allergens related independently to FeNO ( P = .02), S‐ECP ( P = .006) and periostin ( P = .004), whereas sensitization only to airborne allergens related only to FeNO ( P = .02) after adjustments for age, sex, height, weight and smoking history. FeNO correlated weakly with S‐ECP ( r = .17, P < .001), periostin ( r = .19, P < .001) and U‐EDN (0.16, P < .001). S‐ECP also correlated weakly with U‐EDN ( r = .12, P = .02). None of the correlations between the remaining pairs of markers of type 2 inflammation were significant. Conclusions & Clinical Relevance: Sensitization to food allergens related to several local and systemic type 2 inflammation markers, such as FeNO, S‐ECP and periostin. Assessing the profile of allergic sensitization, including to food allergens, might improve the understanding and interpretation of inflammatory markers and potentially improve asthma management.